Typification of thirty-two names given by Alexis Jordan in the genus Biscutella (Brassicaceae) - Thiebaut, Melanie; Tison, Jean-Marc (Phytotaxa, 2016)
This work is a stage of a larger and essential process of typification of A. Jordan’s micro-species. In 1864, this great botanist described 37 species of Biscutella L. (Brassicaceae) in his “Diagnoses d’espèces nouvelles ou méconnues”. Our typification work consisted in searching sheets of Biscutella in Jordan’s herbarium, in LY and in other European herbaria. Finally, seven previously unknown holotypes, 17 lectotypes and eight neotypes have been identified or cited. Furthermore, 14 isolectotypes and eight syntypes have also been mentioned. The only untypified “jordanonˮ is B. collina Jord. of which no reliable specimen could be found.